Belo horror: podem imagens de mulheres falarem a mulheres? - Rodrigues, Ariel de Paiva (Universidade Federal de São Carlos, 2023)
The following work describes the process of carrying out an experimental video-essay that, based on the seminal work by Laura Mulvey, Visual Pleasure and Narrative Cinema, that inaugurates feminist thought in cinematographic studies, seeks in the two versions of Suspiria — both the original 1977 film, directed by Dario Argento, and its 2018 remake, by Luca Guadagnino — a reflection on the representation of the female body in cinema. Based on theoretical research and a bibliographical review of works on female representation and on different video-essay formats, we seek to elaborate an audiovisual product that explores the link between the female body and its images — provoked by these two films — without necessarily relying on a “thesis” to be proved. The goal is to launch a sort of initial questioning and let the editing, in itself, provoke reflection in the viewers.
Beautiful horror: can images of women speak to women?
Keywords: Vídeo-ensaio; Suspiria; Feminismo no cinema; Guadagnino; Argento; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA